Corrosion behaviors of Cr2AlC/α-Al2O3 composites in 3.5 wt. % NaCl aqueous solution. Issue 8 (1st June 2020) - Zhang, Zerong; Qian, Yuhai; Xu, Jingjun; Zuo, Jun; Li, Meishuan
Abstract: Cr2 AlC and its composites containing α-Al2 O3 (6.1 and 15.2 wt %) were prepared by hot pressing and their corrosion behaviors in air-saturated 3.5 wt % NaCl aqueous solution were investigated by electrochemical testing methods. It was revealed that the secondary phase of Al2 O3 particles mainly distributed along grain boundaries of Cr2 AlC matrix. The potentiodynamic polarization measurements showed that the corrosion current densities of these Cr2 AlC composites were lower than that of the pure Cr2 AlC. The Aluminum in Cr2 AlC was prone to be attacked more easily. When immersed at open circuit potential (OCP), Al readily slipped out from Cr2 AlC matrix into NaCl solution in the form of dissoluble species. But in the case of polarization, regardless of potentiostatic polarization or potentiodynamic polarization, more de-intercalated Al, reacted with the electrolyte to form corrosion products of Al2 O3 and/or AlOOH and deposited on the sample surface. For Cr2 AlC/α-Al2 O3 composites, the presence of Al2 O3 weakened the corrosion along grain boundaries by partly blocking the permeation of electrolyte and inhibiting the anodic dissolution process.